The impact of artificial intelligence integration on students' learning motivation and creative expression in visual arts education - Heldayani, Lusi; Heldi , Heldi; Indryuda, Indryuda (Jurnal Sinar Edukasi, 2026)
Learning the visual arts has seen substantial changes as a result of the advancement of artificial intelligence (AI) technology. The purpose of this investigation is to evaluate the impact of AI utilization on the motivation and creativity of students at SMA Negeri 3 Solok Selatan. Employing a quasi-experimental design (one-group pretest-posttest), the investigation implemented a quantitative methodology. A total of 33 students from class XI.8 comprised the research sample. The research instruments comprised a learning motivation questionnaire and a creativity assessment rubric that was based on the characteristics of fluency, flexibility, originality, and elaboration. Descriptive statistics and paired t-tests were implemented to analyze the data. The results suggest that the utilization of AI has a substantial and beneficial impact on both student motivation and creativity. These results indicate that the incorporation of AI into visual arts education can be a successful pedagogical innovation that enhances the quality of the learning process and student outcomes.